Publication of Propaganda Literature by Lithuanian Nationalists in the USA in 1942–1944: Timeless Lithuania, the Book by Owen J. C. Norem - Skirius, Juozas (Knygotyra, 2024)
On the grounds of archival sources and the Lithuanian mass media in the USA at the times, the efforts of the Lithuanian Nationalist Union in 1942–1944 to publish in the USA the book Timeless Lithuania by Owen J. C. Norem, the last American Envoy Extraordinary in Lithuania (1937–1940) as a propaganda instrument are investigated. The research has determined why specifically this book was selected for publication. First of all, it was given preference because of the respectful attitude of Norem towards the history of Lithuania, along with his personal experiences in witnessing the sufferings experienced by the neighboring countries and the consequences of the Soviet occupation for the Lithuanian nation. Besides, the American Lithuanian diaspora was seeking to involve the author of the book into their political activity. The preparation of the book for publication and the process of publishing revealed the organizational and financial difficulties experienced by the activists as well as the issues encountered in preparing the book for publication. The problems were resolved not only by the leaders of the Union for the Liberation of Lithuania, run by the Lithuanian Nationalist Union, but also by Prof. Kazys Pakštas, Antanas Smetona and Lithuanian diplomats in the USA who were also involved in the process. The book played an important role in reviving the Lithuanian diaspora in the USA and seeking attention from the political establishment of the USA. The key source of the research is the correspondence among Lithuanian Nationalists residing in the USA, the author of the book, Antanas Smetona and Lithuanian diplomats; this source has not been used in previous academic research.